Strategi Komunikasi Kesehatan sebagai Upaya Membangun Partisipasi Publik dalam Program Cek Kesehatan Gratis (CKG) di Puskesmas Penjaringan Tahun 2025 - Yuyun Wahyuni; Sri Siswani (JURNAL BIDANG ILMU KESEHATAN, 2025)
CKG is one of the preventive measures implemented by the Penjaringan Community Health Center to detect non-communicable diseases at an early stage. However, community participation in this program is still relatively low, especially among lower-middle-income groups. This study aims to analyze the effectiveness of the health communication strategies implemented, identify the factors influencing the success of these strategies, and formulate an effective communication model to enhance public participation. The methods used include qualitative descriptive approaches through in-depth interviews, direct observation, document review, and Focus Group Discussions (FGD) with healthcare workers, community health workers, and community representatives. The research results indicate that social media is effective in reaching the middle-to-upper economic groups, but less optimal for low-income communities who are more responsive to interpersonal communication and community-based approaches. Key factors determining the success of communication strategies include target segmentation, the role of community health workers, consistency of information, and the community's perception of health services. The most effective communication model is a combination of community-based two-way communication and the use of digital media tailored to the characteristics of the target audience. These findings indicate the need for inclusive, participatory, and locally data-driven communication strategies to enhance community trust and participation in health service programs.